Analisis Kinerja Usahatani Perkebunan Kelapa Sawit Rakyat Melalui Pola Kemitraan di Provinsi Kalimantan Tengah - Suharno Suharno; Yuprin A.D. Yuprin A.D.; Betrixia Barbara (Departmen of Agribusiness, Economics and Management Faculty, Bogor Agricultural University, 2015)
There are three models of partnership in the development of smallholders plantation of palm oil in Center of Kalimantan Province, those are: (1) inti-plasma model that is managed by cooperative; (2) inti-plasma model that is managed by company; (3) inti-plasma model that is managed by individual farmers. This research aims to find the best partnership model amongst them. This research has been done in Kotawaringin Barat District for the first and the third type of models and in Katingan District for the second type. Collecting data and informations was done by Focus Group Discussion (FGD) and interviewed to the farmer respondents. A random sampling of 30 farmers was chosen for the first and the second models. For the second model, all of the farmers who follow the program as many as 20 farmers was chosen as this research respondent. The research found that the first type of those models is the best amongst of the partnership models because of following reasons: (1) highest productivity, about 20 tonnes FFB/ha/year; (2) highest farmer income about Rp 15,682,711/ha/year; (3) business risks are shared by all of the cooperative members; (4) there is guarantee of the input supply and marketing of farming yied from company as a business partner; (5) farmers have some opportunities to increase their household income as company workers or through the other activities. This research recommends to the Government of Kalimantan Tengah Province to oblige the plantation companies to implement an inti-palsma partnership model that is managed by cooperative for whom obligation to develop about 20% of their plantation area for smallholders.